Curso de Pedagogia em EaD do Programa UAB-Moçambique no contexto de uma Cooperação Internacional Sul-Sul: pressupostos para a construção do currículo de formação - Gonzaga, Kátia Valéria Pereira (2017)
This research has as its background the International Educational Cooperation between Brazil and Mozambique, of the South-South type, of strengthening the EAD and the expansion of Higher Education of Mozambique, whose strategy was the shared management of four higher EaD courses, UAB system and Mozambican universities. We delimit study the construction of the curriculum of formation of the course of Teacher Training for Basic Education (Pedagogy), from the analysis of its Pedagogical Project (PP). In addition to interpreting the context of the relations of cooperation, and its reflections in the curricular conceptions and practices proposed, in the course investigated, from some of its stakeholders (a restricted universe of pedagogical course managers, managers of Universities and Teaching Systems of the two Countries). Research is Qualitative, Descriptive, and Critical based on Cultural Studies that share the commitment to examine cultural practices from the point of view of their involvement with, and within, relationships of power. In a first moment we construct the conceptual base of the discourse / analysis of texts and contexts. Then we read and study the official and legal documents guiding the construction of teacher training curricula and the EaD of the countries in cooperation. In order to reconstruct the context through the dialogue between the multiple voices of the research subjects, including that of the researcher, as part of this universe, present in the field records of the Executive Coordination and Local Coordination of the Project (reports, scientific publications, Evaluation, and semi-structured face-to- face and online interviews) and their respective analyzes in order to answer the study questions. In this research, the challenge was to create the enabling environment to establish these dialogues emanating from texts and contexts, respecting their subjectivities and historical contexts of their productions. Thus, to give coherence to the political and epistemological positions that inspire the analysis proposed by the Cultural Studies, the option by the research method was DIY. The results were the critical description of the context investigated with its possibilities and limitations, and the consequent construction of epistemological, political, ethical-cultural and pedagogical presuppositions for other experiences similar to the one studied, in order to value the successful steps in the Direction of the purpose of the cooperation under study, and of overcoming obstacles that have arisen in the development of this, starting from movements already initiated in the course of the 2012-2014 biennium